On ＂LP＂-sasakian manifolds with a coefficient α satisfying certain curvature conditions - De, Krishnendu (Tamsui Oxford Journal of Mathematical Sciences)
The object of the present paper is to classify an ＂LP＂-Sasakian manifold with a coefficient α satisfying certain curvature conditions. Also ξ-concircularly flat and φ-concircularly flat ＂LP＂-Sasakian manifold with a coefficient α have been studied. Finally, we have shown the applications of such a manifold in general relativity and cosmology.